Prokineticin-2 is associated with metabolic syndrome in a middle-aged and elderly Chinese population. Issue 1 (December 2016) - Wang, Yong; Guo, Xiaoyan; Ma, Heng; Lu, Lin; Zhang, Ruiyan
Abstract Background Prokineticin-2 is confirmed to be involved in the inflammatory process. Inflammation plays an important role in the pathogenesis of metabolic syndrome (MS). However, whether prokineticin-2 is associated with MS or not remains unknown. Thus, we present this study to explore the association between prokineticin-2 and MS in a Chinese population. Methods This study included 162 middle-aged and elderly Chinese patients with cardiovascular risk factors. The relationship between serum prokineticin-2 levels and various cardiometabolic risk factors, and MS were evaluated. Results The participants with serum prokineticin-2 levels >6.32 ng/ml had increased waist circumference, body mass index (BMI), plasma triglyceride, diastolic blood pressure (DBP), blood glucose, and serum uric acid, but decreased age, plasma high-density lipoprotein cholesterol (HDL-C), and HDL-C/total cholesterol (TC) (allP < 0.05). A higher percentage of them had history of lipid disorders (19.3 vs 2.5 %, P = 0.001) and MS (77.1 vs 48.1 %, P < 0.001). Prokineticin-2 was positively correlated with TC (partial correlation coefficient: 0.233, P = 0.011), triglyceride (partial correlation coefficient: 0.504, P < 0.001), fasting plasma glucose (partial correlation coefficient: 0.336, P < 0.001), HbA1c (partial correlation coefficient: 0.285, P = 0.002), and uric acid (partial correlation coefficient: 0.234, P = 0.011) respectively, but was negatively correlated with HDL-C/TC (partial correlation coefficient: −0.269, P = 0.003) with adjustment for age, man, and BMI. Prokineticin-2 was significantly elevated in participants with MS (7.72 ± 3.34vs 5.56 ± 2.39 ng/ml, P < 0.001). Furthermore, prokineticin-2 was significantly elevated in participants with increased numbers of MS components (5.17 ± 2.29vs 5.94 ± 2.47vs 7.13 ± 3.33vs 8.32 ± 2.81vs 9.82 ± 4.37 ng/ml, P for trend <0.001). Multiple logistic regression analysis indicated that prokineticin-2 was independently associated with MS (OR: 1.307, 95 % confidence interval: 1.127–1.515, P < 0.001) with adjustment for other potential confounders. If serum prokineticin-2 value can be considered as an indicator to discriminate MS, receiver operating characteristic curve analysis exhibited the area under the curve as 0.701. Conclusions Prokineticin-2 is correlated with various cardiometabolic risk factors including blood lipid, blood glucose, blood pressure, BMI, and uric acid. And furthermore, the increased prokineticin-2 is independently associated with MS.